2022
DOI: 10.3389/fimmu.2022.809837
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics, Oncogenic Roles, and Relevant Immune and Pharmacogenomic Features of EVA1B in Colorectal Cancer

Abstract: ObjectiveEVA1B, a protein coding gene, is a critical paralog of EVA1A gene. Herein, our study was conducted to investigate the role of EVA1B in colorectal cancer (CRC) progression and prognosis.MethodsPan-cancer analysis was conducted to analyze expression, genetic and epigenetic alterations, and immunological characteristics of EVA1B. Especially, immunological characteristics and mutational landscape were compared between high and low EVA1B expression groups in the combined TCGA-COAD and TCGA-READ datasets. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Surgical resection combined with chemotherapy is presently the preferred therapeutic strategy for most patients with advanced cancer [ 38 ]. Clinical trials are underway to explore immunotherapy as a supplementary curative and palliative treatment, potentially offering a novel strategy for patients with advanced or inoperable disease [ 39 , 40 ]. However, the development of precision and individualized tumor therapy is somewhat constrained by the lack of effective diagnostic and therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection combined with chemotherapy is presently the preferred therapeutic strategy for most patients with advanced cancer [ 38 ]. Clinical trials are underway to explore immunotherapy as a supplementary curative and palliative treatment, potentially offering a novel strategy for patients with advanced or inoperable disease [ 39 , 40 ]. However, the development of precision and individualized tumor therapy is somewhat constrained by the lack of effective diagnostic and therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in BC cells and tumor tissues, FBLN5 expression downregulates the activation of the NF-κB signaling pathway to promote BC cell proliferation and migration ( 32 ). Studies have shown that EVA1B expression is upregulated in colon cancer and glioma ( 33 , 34 ). However, few EVA1B-related studies have been found in BC.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the TROAP expression level and these processes was also confirmed. Finally, the immune checkpoints were extracted from previous studies to explore the relationship between TROAP and immune checkpoints 40–43 …”
Section: Methodsmentioning
confidence: 99%
“…TROAP‐relevant genes with p value < 0.05 were determined as prognostic factors, which were input into the out‐of‐bag data (OOB) algorithm to obtain essential variables with the minimum value of OOB. Finally, the gene set with the highest accuracy was confirmed by the SVMRFE machine algorithm, and a prognostic model was constructed using multivariate Cox regression analysis 40 . The TROAP‐relevant risk score was calculated according to the expression and regression coefficient of the model gene.…”
Section: Methodsmentioning
confidence: 99%